Okiełznać dziki Ru.net. Internet a przemiany gatunkowe w literaturze rosyjskiej - Mięsowska, Lidia; Pawletko, Beata (Rusycystyczne Studia Literaturoznawcze, 2008)
The article is an attempt to describe the phenomena characteristic of e-culture which more and more commonly becomes an alternative to traditional approach to culture. On the basis of the latest Russian literature the authors present the effects of the symbiosis of printed literature, multimedia and the Internet subculture. Sample genological changes, which occurred within the chosen literary genres influenced by the internet-related forms of communication, are discussed. The conducted analyses show that the most significant changes take place in drama genres where the elements of structure and internet-related means of communication (i.e. chat, forum, computer games) are used. The influence of multimedia on literature can be observed in the newly appeared genres such as: tanquette, reality drama, drama-chat etc.), especially when authors refer to the specific likings of internet clubbing society. Furthermore, it results in the change of the writer-reader relationship which becomes more interactive in character whereas the genre itself is transformed into a specific form of experiencing the world and becomes an aesthetic category.